Reading America : Citizenship, Democracy, and Cold War Literature. - Matthews, Kristin L. (University of Massachusetts Press, 2017)
"During the Cold War, the editor of Time magazine declared, "A good citizen is a good reader." As postwar euphoria faded, a wide variety of Americans turned to reading to understand their place in the changing world. Yet, what did it mean to be a good reader? And how did reading make you a good citizen? In Reading America, Kristin L. Matthews puts into conversation a range of political, educational, popular, and touchstone literary texts to demonstrate how Americans from across the political spectrum--including "great works" proponents, New Critics, civil rights leaders, postmodern theorists, neoconservatives, and multiculturalists--celebrated particular texts and advocated particular interpretive methods as they worked to make their vision of "America" a reality. She situates the fiction of J.D. Salinger, Ralph Ellison, Thomas Pynchon, John Barth, and Maxine Hong Kingston within these debates, illustrating how Cold War literature was not just an object of but also a vested participant in postwar efforts to define good reading and citizenship"--